2015
DOI: 10.3390/ma8063767
|View full text |Cite
|
Sign up to set email alerts
|

Liquid- and Gas-Phase Diffusion of Ferrocene in Thin Films of Metal-Organic Frameworks

Abstract: The mass transfer of the guest molecules in nanoporous host materials, in particular in metal-organic frameworks (MOFs), is among the crucial features of their applications. By using thin surface-mounted MOF films in combination with a quartz crystal microbalance (QCM), the diffusion of ferrocene vapor and of ethanolic and hexanic ferrocene solution in HKUST-1 was investigated. For the first time, liquid- and gas-phase diffusion in MOFs was compared directly in the identical sample. The diffusion coefficients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 44 publications
(49 reference statements)
2
21
2
Order By: Relevance
“…For example, it would take more than a year for a 50 µm MOF crystal to uptake molecules with a diffusion coefficient of 10 −18 m 2 s −1 . [31] Taking advantage of the optical transparency of high-quality SURMOFs allows the investigation of multicomponent, i.e., binary and ternary mixture, uptake of dye molecules. [27] Several previous works demonstrated that SURMOFs are ideal to serve as model systems for studying diffusion in nanoporous frameworks (Figure 4).…”
Section: Unique Model System For Diffusion Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it would take more than a year for a 50 µm MOF crystal to uptake molecules with a diffusion coefficient of 10 −18 m 2 s −1 . [31] Taking advantage of the optical transparency of high-quality SURMOFs allows the investigation of multicomponent, i.e., binary and ternary mixture, uptake of dye molecules. [27] Several previous works demonstrated that SURMOFs are ideal to serve as model systems for studying diffusion in nanoporous frameworks (Figure 4).…”
Section: Unique Model System For Diffusion Experimentsmentioning
confidence: 99%
“…[30] The rigid attachment of SURMOF samples to the solid support also permits investigations of the uptake from the liquid and gas phases by the very same sample. [31] Taking advantage of the optical transparency of high-quality SURMOFs allows the investigation of multicomponent, i.e., binary and ternary mixture, uptake of dye molecules. [32]…”
Section: Unique Model System For Diffusion Experimentsmentioning
confidence: 99%
“…By means of liquid-phase epitaxy, surface-mounted MOFs (SURMOFs) can be directly prepared on the solid substrate surface. 27,28 Two pillared-layer MOF structures based on organic linker molecules with azobenzene side groups are investigated: Cu 2 (BDC) 2 (AzoBiPyB) and Cu 2 (DMTPDC) 2 (AzoBiPyB) (AzoBiPyB: 4,4 0 -(2-(phenyldiazenyl)-1,4-phenylene)dipyridine); 29 BDC: benzene-1,4-dicarboxylic acid, DMTPDC: 2,2 00 -dimethyl-[1,1 0 :4 0 ,1 00 -terphenyl]-4,4 00 -dicarboxylic acid, see ESI † (SI1). 25 Furthermore, SURMOFs can be studied in a straightforward fashion by surface-sensitive spectroscopic techniques like X-ray photoelectron spectroscopy (XPS) 26 and infrared reflection-absorption spectroscopy (IRRAS).…”
Section: Introductionmentioning
confidence: 99%
“…By using the SURMOF approach, the film can be grown directly on the QCM sensor, allowing the direct real-time quantification of the mass during the synthesis. By connecting the QCM to a liquid-or gas-flow system, the molecular uptake by the SURMOF from the liquid or gas phase can be measured [41,42]. Taking advantage of the mass quantification by QCM, the uptake in units of guest molecules per MOF pore (or per unit cell) can be directly calculated.…”
Section: Precise Uptake Measurements Using a Quartz Crystal Microbalamentioning
confidence: 99%